Implementing reflection in GHC - Tanaka, Jiro (1990)
Abstract: "Implementation of reflection in GHC is presented in this paper. Though GHC is an [sic] parallel dialect of Prolog, we can regard it as a parallel object-oriented language since it has the notion of object and communication between objects. After reviewing the language features of GHC as a parallel object-oriented language, we consider the realization of GHC meta-computation system first. Based on the meta-level representation of GHC, an enhanced GHC meta-program is proposed. Then we propose Reflective GHC, where reflective tower can be constructed and collapsed in a dynamic manner using reflective predicates. Reflective GHC has actually been implemented. All codes shown in this paper are running on our Reflective GHC system."
Keywords: GHC (Computer program language)